2009
DOI: 10.1038/jcbfm.2009.113
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Transient Peripheral Inflammatory Response Precedes Brain Inflammation after Experimental Stroke

Abstract: Increasing evidence suggests that peripheral inflammatory responses to stroke and other brain injuries have an important role in determining neurological outcome. The mediators of this response and the temporal relationships between peripheral and central inflammatory alterations are poorly understood. In this study, we show that experimental stroke in mice induces a peripheral inflammatory response that peaks 4 h after stroke, and precedes the peak in brain inflammation 24 h after stroke. This peripheral resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 15 publications
5
88
1
Order By: Relevance
“…Interestingly, recent studies have shown that experimental stroke in mice induces a systemic inflammatory response that precedes an inflammatory response in the brain, with a strong contributory role for the chemokine CXCL-1. 38 Other recent studies have shown that peripheral IL-1b challenge exacerbates injury via a mechanism that is neutrophildependent after experimental stroke in mice 11 and that microglia/ macrophages, associated with EAE lesions in rat, respond to circulating cytokines, and produced in response to an inflammatory event lead to tissue damage and axon injury. 14 Effect of AdIL-1b on Magnetic Resonance Imaging Signal Changes To use clinically applicable measures of lesion reactivation rCBV, MTR and tissue water diffusion were measured by MRI over a 5-day period after injection of AdIL-1b, during which time systemic expression of IL-1b is maximal.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, recent studies have shown that experimental stroke in mice induces a systemic inflammatory response that precedes an inflammatory response in the brain, with a strong contributory role for the chemokine CXCL-1. 38 Other recent studies have shown that peripheral IL-1b challenge exacerbates injury via a mechanism that is neutrophildependent after experimental stroke in mice 11 and that microglia/ macrophages, associated with EAE lesions in rat, respond to circulating cytokines, and produced in response to an inflammatory event lead to tissue damage and axon injury. 14 Effect of AdIL-1b on Magnetic Resonance Imaging Signal Changes To use clinically applicable measures of lesion reactivation rCBV, MTR and tissue water diffusion were measured by MRI over a 5-day period after injection of AdIL-1b, during which time systemic expression of IL-1b is maximal.…”
Section: Discussionmentioning
confidence: 98%
“…Our results also show a reduction in the expression of vascular-and neutrophil-associated MMP-9 and a reduction in BBB damage with a delayed administration of IL-1Ra (3 hours of reperfusion) in older lean animals. Increases in neutrophil infiltration after stroke could be driven by microglialderived IL-6 and CXCL1 (Chapman et al, 2009;McColl et al, 2007;Rodriguez-Yanez and Castillo, 2008), both of which are increased by systemic inflammation. This is also demonstrated by our results, where aged and comorbid animals show higher expression of microglial-associated IL-6 and CXCL1 after stroke, an effect again reversed centrally but not peripherally by IL-1Ra in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has consistently described stroke-induced early peripheral immune activation, which is defined by increased inflammatory cytokines in both experimental animal models and humans [10][11][12][13]. This early immune activation often progresses to immune suppression in patients with stroke.…”
Section: Impact Of Stroke On Immunitymentioning
confidence: 99%